Valorization of oil palm by-product materials as a new sustainable carbon source for carbon-based nanomaterial synthesis and energy storage application - Nasir, Salisu (2019)
Energy and environmental issues are the two major problems that our world is facing today. These, combined with developing consumer demands have stirred researchers’ interest in inexpensive, environmentally friendly functional materials. With Malaysia as an indicator, and based on a projected annual production of palm oil in Malaysia of over 15.4 million metric tons by 2020, it is estimated that about 46.6 tons of lignocellulosic wastes will be generated. Transforming these wastes into wealth could be integrated into a global paradigm shift towards sustainable development.